Comparative analysis of chloroplast genomes in three Araceae species: genomic difference, genetic distance and species morphology association - Li, Wengang; Liu, Jingru; Wang, Siqin; Ma, Ying; Cui, Lulu; Yao, Yingxian; Sun, Ke; Luo, Lili (Frontiers in Genetics, 2025)
Many species in the Araceae have extremely high medicinal value, while the chloroplast genome is relatively conserved, and the encoded and expressed bioactive substances are also abundant. Therefore, chloroplast genomes can serve as one of the basis for species evolution and are extremely important for individual material accumulation. To study the relationship between the chloroplast genome and morphology of target species, this study selected three Araceae species for chloroplast genome sequencing assembly, downloaded the complete chloroplast genomes sequences of another 11 Araceae species. Grouping based on genetic distance, we analyze the association between chloroplast genome structure and morphology. The results showed that there were significant differences in genome size among the three species, but Relative Synonymous Codon Usage (RSCU) exhibited high similarity; Based on the phylogenetic tree, these 14 species can be divided into three branches, with differences in genes such as rrn4, rrn5, rrn23, and trnN among species within each branch; Morphologically, the length of the male inflorescence in BranchⅢ is significantly greater than that in BranchⅡ; There is a strong positive correlation between the length of the plant stem and the three parameters (Length of LSC, Length of SSC and Length of chloroplast genome) of the genome. This study conducted correlation research from the perspective of chloroplast genome and species morphology. On the one hand, the genetic distance and chloroplast genome structure differences between the target species were determined, and on the other hand, explored the correlation between chloroplast genome and species morphology, providing a theoretical basis for the study of phylogenetic relationships and morphology of Araceae species.